On the properties of identified dopaminergic neurons in the mouse substantia nigra and ventral tegmental area. (11th September 2016) - Krashia, Paraskevi; Martini, Alessandro; Nobili, Annalisa; Aversa, Daniela; D'Amelio, Marcello; Berretta, Nicola; Guatteo, Ezia; Mercuri, Nicola Biagio
Abstract: We studied the properties of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and ventral tegmental area (VTA) in mice expressing the enhanced green fluorescent protein (eGFP) under the control of the tyrosine hydroxylase promoter (TH‐GFP). By using a practical map of cell positioning in distinct SNpc and VTA subregions in horizontal midbrain slices we saw that the spontaneous firing, membrane properties, cell body size and magnitude of the hyperpolarization‐activated current ( I h ) in TH‐GFP‐positive neurons (TH‐GFP + ) vary significantly among subregions, following a mediolateral gradient. Block of I h with Zd7288 inhibited firing in the most lateral subregions, but had little effect in the intermediate/medial VTA. In addition, TH‐GFP + cells were excited by Met 5 ‐Enkephalin. Extracellular recordings from a large neuron number showed that all TH‐GFP + cells were inhibited by dopamine, suggesting that this is a reliable approach for identifying dopaminergic neurons in vitro . Simultaneous recordings from dopamine‐sensitive and dopamine‐insensitive neurons showed that dopamine‐insensitive cells (putative non‐dopaminergic neurons) are unaffected by Zd7288 but inhibited by Met 5 ‐Enkephalin. Under patch‐clamp, dopamine generated a quantitatively similar outward current in most TH‐GFP + neurons, although medial VTA cells showed reduced dopamine sensitivity. Pargyline prolonged the dopamine current, whereas cocaine enhanced dopamine‐mediated responses in both the SNpc and the VTA. Our work provides new insights into the variability in mouse midbrain dopaminergic neurons along the medial–lateral axis and points to the necessity of a combination of different electrophysiological and pharmacological approaches for reliably identifying these cells to distinguish them from non‐dopaminergic neurons in the midbrain. Abstract : We studied the properties of identified DAergic neurons in midbrain slices from TH‐GFP mice. We saw that the firing rate, membrane properties, cell size and I h magnitude of TH‐GFP + cells varied with a mediolateral gradient across distinct SNpc and VTA subregions. TH‐GFP + cells were inhibited by DA and excited by Met‐Enk, whereas Zd7288 inhibited firing only in the most lateral regions. Our work provides new insights into the variability in midbrain DAergic neurons along the mediolateral axis.